Management of tribunal operations : Migration Review Tribunal and Refugee Review Tribunal - Australian National Audit Office (Canberra : Australian National Audit Office, 2007)
The objective of the audit was to assess the effectiveness of the Tribunals' management of their operations.
"Audit team: Steven Lack, Russell Lapthorne, Michelle Hart"--P. 4.
Includes bibliographical references and index.
Also available in an electronic version on the Internet. Address as of 10/08/07: http://www.anao.gov.au/uploads/documents/2006-07_Audit_Report_441.pdf
Keywords: Australia. -- Migration Review Tribunal -- Auditing; Australia. -- Refugee Review Tribunal -- Auditing; Administrative courts -- Australia -- Auditing